Structural features of the aromatic/arginine constriction in the aquaglyceroporin GintAQPF2 are responsible for glycerol impermeability in arbuscular mycorrhizal symbiosis. Issue 1 (January 2017) - Li, Tao; Hou, Wen-Tao; Ruan, Yuan; Chen, Bao-Dong; Yang, Li-Guo; Zhou, Cong-Zhao; Zhu, Yong-Guan
Abstract: Carbon transport in arbuscular mycorrhizal (AM) symbiosis is of fundamental importance. However, the role of glycerol transport in AM symbiosis has not yet been resolved. Glycerol transport across the cell membrane is mediated by aquaglyceroporins (AQGPs), whereas our previous study revealed that it was disfavoured by GintAQPF2, an AQGP from AM fungi (AMF). Here, we analysed the function of two amino acid residues in the aromatic/arginine (ar/R) constriction known as the major selectivity filter in AQGPs. Replacement of phenylalanine-94 (Phe-94) by alanine (Ala) enlarged the diameter of the ar/R constriction and resulted in an increased intracellular glycerol accumulation and thus survival rate of yeast cells at high glycerol levels, while individual or joint replacement of Phe-94 and Ala-234 by tryptophan and glycine induced a closed state of GintAQPF2, suggesting that the potential double gates (Phe94-Phe243 and arginine-249) of the ar/R constriction also likely determined solute permeability. To figure out whether GintAQPF2 functions were relevant to the establishment of AM symbiosis, genomic analyses of four representative fungi with different lifestyles were performed. We found that glycerol facilitators existed in the facultative fungi (the ectomycorrhizal fungus Laccaria bicolor and hemibiotrophic pathogen Magnaporthe oryzae ), but not in the obligatory fungi (the AMF Rhizophagus irregularis and necrotrophic pathogen Fusarium verticillioides ), revealing a conserved pattern of glycerol transport in symbionts and pathogens. Our results suggested that glycerol blocks due to the special structural features of the ar/R constriction in the only AMF AQGP could potentially play a role in the establishment of AM symbiosis. Highlights: The aquaglyceroporin GintAQPF2 from AM fungi disfavoured glycerol transport. Genomes of four representative fungi with different lifestyles were compared. A conserved pattern of glycerol transport in symbionts and pathogens was revealed. Blocked glycerol passage could be involved in the establishment of obligate biotrophy of AM fungi.